Legal Analysis of the Legal Force of Mediation Results as a Dispute Resolution Method in Business Contracts (Based on Law Number 30 of 1999 Concerning Alternative Dispute Resolution) - Glora Meliana Sitohang; Jinner Sidauruk; Sovia Simamora (Journal of Legal and Cultural Analytics, 2025)
Based on Larw Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution, this study examines the legality of mediation outcomes as a dispute resolution procedure in business contracts. Mediation is one alternative dispute resolution technique. By using a mediator as an impartial third party, the two parties to the dispute hope to come to a peaceful resolution. In commercial negotiations, mediation offers benefits since it saves time and money while preserving positive relationships between the parties. This study combines a qualitative analytical method of statutory regulations, legal documents, and related literature with a normative juridical approach. According to the research findings, if the mediation judgment specified in the agreement satisfies specific requirements outlined in Law Number 30 of 1999, it has bonding legal force for both parties. In addition to being signed by the mediator and the parties, the mediation agreement may be presented to a court for approval, or homologation, which grants it executory powers. In addition, this study found a number of elements that affect how well mediation works to settle disputes involving commercial contracts, such as the mediator's skill and reputation, the transparency of the mediation process, and the parties' openness in sharing information and communicating with one another. The analysis's findings led to the conclusion that mediation, when used to settle conflicts in commercial contracts, has a great deal of potential to be an effective and efficient solution, with adequate legal force in accordance with applicable regulations.